Tertawa untuk Kesehatan Fisik dan Mental: Studi Takhrij dan Syarah Hadis Pendekatan Bidang Kesehatan - Fahri Muhamad; Susanti Vera; Putri Anditasari (Gunung Djati Conference Series, 2022)
This study discusses the syarah of hadith related to things that are inherent in human life, namely laughter. This study uses a qualitative approach which is emphasized by literature study through the takhrij and syarah hadith methods using contemporary analysis. The results of this study found that the status of the hadith about laughter was considered valid according to the takhrij hadith, whereas if viewed from the syarah of the hadith it showed that laughter can have a health impact. The conclusion of this study is that the hadith about laughter can be used as reference material in health therapy because it has a valid status and laughter can be used to reduce human stress levels and can strengthen the body's immunity on a daily basis in accordance with the instructions in the health sector, this study recommends collaboration between hadith experts, health professionals and psychologists to experiment in the management of laughter therapy for people who have high-stress levels.